Aquaponics system for treat a catfish wastewater - Nurain, Abu Hasan (2014)
The combination of fish and plant production in an integrated recirculation system is called Aquaponics System. In natural waters, ammonium is converted rather rapidly to nitrite and further to nitrate by aerobic bacteria from the genera Nitrosomonas and Nitrobacter, through a process called nitrification. Ammonia (NH3) is the waste products of the fish and extremely toxic to fish. First nitrifying process is by Nitrosomonas bacteria. Nitrosomonas bacteria is cultured in the grow beds (gravel). This bacteria feed on both oxygen' and ammonia and with their biological activities. Reaction of Nitrosomonas bacteria produces excretes a chemical called nitrite (NO2). Nitrite is toxic to fish but not toxic as ammonia. Second of nitrifying process is by Nitrobacter bacteria. Nitrobacter bacteria also cultured in the grow beds (gravel). These bacteria utilize oxygen in its respiration, acts in similar way as Nitrosomonas bacteria. Reaction of Nitrobacter bacteria have changes the nitrite into a relatively harmless chemical called nitrate (NO3). Nitrate is primary source of plant nutrition. Plants take in the converted nirates as nutrients. The nutrients are a fertilizer, feeding the plants. This system produces the clean water to fish tank and ready for next cycle. The aims of this research are to determine the characteristics of water quality from the cultured catfish (Siluriforme) tank, to determine effect of vegetable (Ipomoea aquatic) distribution on the wastewater quality and effect of the vegetable (Ipomoea aquatic) growth. The results found the ideal range of temperature 27.92°C to 29.14°C and ideal range of pH 6.50- 6.94. The temperature and pH in fish tank in controlled conditions. Besides that, the results of BOD5, COD, TSS and N}14 - N concentration have decrease responding to retention time. It is because of nitrifying process and the growing root of plants and increasing the plants in Aquaponics. Besides that, Ipomoea aquatic grow rapidly and seemed healthy.